PRODUKSI PROTEIN SEL TUNGGAL (PST) SPIRULINA SP. SEBAGAI SUPER FOOD DALAM UPAYA PENANGGULANGAN GIZI BURUK DAN KERAWANAN PANGAN DI INDONESIA - Amanatin, Dwi Riesya; Rofidah, Erna; Nasiqiati Rosady, Siti Duratun (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Tauge Extract Medium (TEM) and urea can be a good choice in developing the culture of Spirulina sp., because in addition to lower cost also has deposits of macronutrient and micronutrients that support the nutritional content of Spirulina sp. This research aims to know the right combination concentration of TEM Â and urea that can produce the highest levels of a protein. Combination executed is as follows: P1 : 2% TEM 80 ppm urea, P2 : 2% TEM 100 ppm urea, P3 : 2% TEM 120 ppm urea, P4 : 4% TEM 80 ppm urea, P5 : 4% TEM 100 ppm urea, P6 : 4% TEM 120 ppm urea, P7: 6% TEM 80 ppm urea, P8: 6% TEM 100 ppm urea, P9: 6% TEM 120 ppm urea, and P10 : walne (control). ANOVA test results (P<0,05) indicates that there is influence of TEM and urea with the protein of Spirulina sp. then test results of Dunnet test showing that P5 have a real difference against control with levels of 20,557 % protein in phase stationary and 19,220 % in phase exponentially. This provides indication that combination of TEM and urea has the potential to become as alternativesÂ fertilizer in Spirulina sp. culture. To acquire levels of high protein and low cost of fertilizer. So it can be applied in the production of single cell protein of Spirulina sp. as a super food.Keywords: Spirulina sp., Urea Fertilizer, Tauge Extract Medium (TEM) proteins, Super food